Sketch for a systematic metaphysics - Armstrong, D. M. (David Malet), 1926- (Oxford : Clarendon, 2010)
David Armstrong sets out his metaphysical system in a set of concise and lively chapters each dealing with one aspect of the world. On the basis of the assumption that all that exists is the physical world of space-time, he constructs a coherent metaphysical scheme that gives plausible answers to many of the great problems of metaphysics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics